Characterization of aluminum alloy-epoxy bonded joints with nanofibers obtained by electrospinning. Issue 1 (11th March 2020) - Cocchi, D.; Musiari, F.; Brugo, T. M.; Pirondi, A.; Zucchelli, A.; Campanini, F.; Leoni, E.; Mazzocchetti, L.
ABSTRACT: In previous works, the authors showed that nylon nanofibers in the form of a random mat (nanomat) obtained by electrospinning can be used in bonded joints, where they may also work as an adhesive carrier. In those works, the setup of the bonding procedure started from a low-viscosity epoxy resin for hand layup in order to facilitate wetting of the nanomat, then a medium viscosity, two-component, unfilled epoxy adhesive was employed as an intermediate development step towards the addition of the nanomat to a high-viscosity, high strength, two-component epoxy adhesive system. The present work is therefore aimed at analyzing the performance of an epoxy adhesive for structural bonding, modified with the addition of a nylon nanomat generated by electrospinning. The adhesive is mixed and air bubbles are evacuated, then the nanomat is immersed in the adhesive, gently squeezed through two adjacent drums, counter-rotating at a given distance, in order to eliminate excess adhesive and to calibrate the wet nanomat thickness. The wet nanomat strip is finally placed between AA 6082-T4 adherents and let to consolidate to obtain Double Cantilever Beam (DCB) bonded specimens. Fracture tests are performed and the mode-I fracture toughness with and without the nanomat is compared.